Estimation of mean glandular doses in mammography of patients aged 40 to 64 using Dance factors. HNAAA - Paredes López, Lilian Roxana (2017)
The aim of this research was to estimate the Glandular Dose (DGM), using the conversion factors reported in the Dance tables. The Kerma in air (ESAK) and the Inlet Surface Dose ( ESD), for which we worked with the mammography equipment brand LORAD - HOLOGIC of the Radiodiagnostic Service of the National Hospital "Almanzor Aguinaga Asenjo" and also requested the Technical Report of Quality Control of this equipment. Data were collected from 54 women between 40 and 64 years of age (restriction imposed by the values given by Dance and Cols.), Volunteers undergoing mammography examinations at the Hospital "Almarzor Aguinaga Asenjo", considering age, kilovoltage (kV), Load (mAs), anode-filter combination (Mo- Mo), focus-film distance and breast thickness of patients in caudal skull projection. Taking these data, the Glandular Dose (DGM) for each patient was found, with 40 to 49 and 50 to 64 year old women, with a 95% confidence interval and correlation of the data 0.68 (T-test). The result obtained for DGM is 2.3mGy, which is below the limit established by the European Dosimetry Protocol (3mGy).